Tester selection for combining ability estimation of storage root yield and sweetpotato virus disease in sweetpotato breeding - Swanckaert, J.; Santos, I.G.D.; Chaves, S.F.S.; Ssali, R.T.; Mwanga, R.O.M.; Azevedo, C.F.; Mendes, T.; Boeck, B. de; Eyzaguirre, R.; Kitavi, M.; Gemenet, D.; Andrade, M.I.; et al. (2025)
General combining ability (GCA) is the major selection criterion for new sweetpotato (Ipomoea batatas) parents in a reciprocal recurrent selection (RRS) scheme. Here we aimed to estimate GCA and specific combining ability (SCA) by using 16 potential testers involved in an 8 × 8 partial diallel and propose a procedure to identify testers in sweetpotato breeding. Data on storage root yield in tons per hectare (rytha), and sweetpotato virus disease (vir2) from 64 families (1,913 clones) were collected in five trials at two locations in Uganda. The estimates of the female GCA accounted for the largest additive genetic variation for storage root yield compared to the male GCA for both traits. Mid-parent heterosis ranged from − 6.2 to 7% for rytha, and − 1.1 to 1.3% for vir2 in the progeny families. A stepwise procedure to identify testers top-ranked ‘NASPOT 7’ as a dual tester for both traits. Besides this parent, ‘Ejumula’ and ‘NASPOT 10 O’ for rytha, and ‘NASPOT 1’, ‘NK259L’, ‘SPK004’, and ‘NASPOT 11’ for vir2 are particularly suitable as respective single-trait testers. Testers are important in many plant breeding programs to enhance efficiency of RRS, and thus other crop species might benefit from the strategy and methods applied herein.